Real-time out-of-core visualization of particle traces - Bruckschen, R.; Kuester, F.; Hamann, B.; Joy, K.I. (IEEE Parallel and Large Data Visualization and Graphics Symposium 2001, 2001)
Visualization of particle traces provides intuitive and efficient means for the exploration and analysis of complex vector fields. The paper presents a method suitable for the real-time visualization of arbitrarily large time-varying vector fields in virtual environments. We describe an out-of-core scheme in which two distinct pre-processing and rendering components enable real-time data streaming and visualization. The presented approach yields low-latency application start-up times and small memory footprints. The described system was used to implement a "volumetric fog lance," which can emit up to 60000 particles into a flow field while maintaining an interactive frame rate of 60 frames per second. All algorithms were specifically designed to support commodity hardware. The proof-of-concept system is running on a low-cost Linux workstation equipped with a 120 GB E-IDE RAID (redundant array of inexpensive disk) system.